A review on traditional uses, phytochemistry, pharmacology, toxicology and the analytical methods of the genus Nardostachys. (15th November 2021) - Wang, Miao; Yang, Tian-Tian; Rao, Yao; Wang, Zhi-Mei; Dong, Xueqi; Zhang, Li-Hua; Han, Lifeng; Zhang, Yi; Wang, Tao; Zhu, Yan; Gao, Xiu-Mei; Li, Tian-Xiang; et al.
Abstract: Ethnopharmacological relevance: The plants of the genus Nardostachys (Caprifoliaceae) have been used for a long history in different cultural systems of medicine, including Chinese, Ayurvedic, Korean folk medicine and Islamic, for treatments of disorders in nervous, digestive, cardiovascular and integumentary systems. Aim of the review: This review aims to provide comprehensive information on Nardostachys plants including botany update, traditional uses, data mining of uses in traditional Chinese medicine (TCM) and current Chinese medicinal patents, chemical constituents, pharmacological effects, toxicity and analytical method studies. Materials and methods: Studies of the genus Nardostachys were collected via Google Scholar and Baidu Scholar, ScienceDirect, SciFinder, Wiley Online Library, ACS Publications, NLM/NCBI, Web of Science, CNKI, WANFANG DATA, EMBASE, Huabeing database and Traditional Chinese Medicine Resource Network and libraries. Some local books, PhD or MS's dissertations were also included. The literatures cited in this review covered the period from 1962 to March 2021. The Plant List and Kew Herbarium Catalogue databases were used to authenticate the scientific name. Results: Botany description of Nardostachys genus is updated. Analysis of the literatures indicates that Nardostachys species are valuable herbs with therapeutic potentials for various disorders. Data mining on ancient TCM prescriptions and current Chinese medicinal patents containing Nardostachys revealed its common compatibility with other herbs in China. Phytochemical studies identified terpenoids and phenolic compounds as the main constituents in the genus Nardostachys and sesquiterpenoids as the major bioactive components. Experimental studies demonstrated that crude extracts, major fractions and the main constituents from Nardostachys species mainly exhibited pharmacological activities on nervous, digestive, cardiovascular and skin systems. Further, in vivo and in vitro toxicological studies demonstrated that Nardostachys plants showed either no or low toxicities, except at high doses. Finally, methods of qualitative and quantitative analyses on chemical constituents of genus Nardostachys were summarized, including TLC/HPTLC, GC and HPLC/UPLC methods, combined with common detectors including PDA, DAD and MS. Conclusions: This review summarizes the progress on phytochemistry, pharmacology, toxicology and analytical methods of the genus Nardostachys . Studies demonstrate traditional uses of the genus Nardostachys, and reveal novel bioactive effects for clinical uses. These achievements expand our knowledge on the genus Nardostachys and its clinical value. Graphical abstract: Image 1